Pemberdayaan masyarakat melalui pengembangan desa mandiri energi (Studi kasus di Klaten Jawa Tengah) - Dita Wahyu Ningtyas T; Suwarto Suwarto; Eny Lestari (Unri Conference Series: Community Engagement, 2020)
This study aims to examine the implementation of the process and impact of community empowerment in the development of an independent village of biogas energy in Mundu Village, Tulung District, Klaten Regency. The results showed that community empowerment in Mundu Village, Tulung District, Klaten Regency has been going on since 2014. Until now, there have been 40 more digester installations installed. Empowerment is carried out with the help of NGO field facilitators and has received several awards. The stages of empowerment are carried out by raising awareness, capacitating and empowering them. Awareness is carried out by making the village aware of the potential of livestock manure waste and overcoming the problem of air pollution caused by slag waste. Capacitating is carried out by providing capacitance to humans (individuals), organizations and value systems, providing guidance in the form of training activities. Trust is given by giving the community full authority to manage biogas. The impact of this empowerment is a change in mindset, work patterns, value systems and business systems.